1997
DOI: 10.1111/1467-985x.00063
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evidence in Discrimination Cases

Abstract: Statistical data and analyses are used as circumstantial evidence indicating that race, gender, age or another legally prohibited factor was a signi®cant cause of an unfavourable employment or governmental decision. This paper discusses the role of statistical evidence in the context of the legal process. Changepoint techniques to determine when an employment practice changed and Corn®eld's approach to examining alleged¯aws in a statistical analysis to ensure that they are suf®ciently severe to affect the ®nal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This early empirical work played a minor role in cases brought to court based on the Equal Pay Act of 1963 and the Civil Rights Act of 1964 but, according to Ashenfelter and Oaxaca (1987), over time became the primary form of analysis for decisions of disparate impact against population subgroups. The U.S. Supreme Court has heard many cases in which statistical evidence of disparate impact discrimination has been admitted in cases involving jury selection and employment discrimination, focusing on factors such as gender, race, and age (see, e.g., Ashenfelter & Oaxaca, 1987;Castaneda v. Partida, 1977;Gunderson, 1989;Hazelwood School District v. United States, 1977;Gastwirth, 1984Gastwirth, , 1997Kaye, 1982;Lee, 1989: Shafritz, Hyde, & Rosenbloom, 1986.…”
Section: The Concept Of Disparate Impactmentioning
confidence: 99%
“…This early empirical work played a minor role in cases brought to court based on the Equal Pay Act of 1963 and the Civil Rights Act of 1964 but, according to Ashenfelter and Oaxaca (1987), over time became the primary form of analysis for decisions of disparate impact against population subgroups. The U.S. Supreme Court has heard many cases in which statistical evidence of disparate impact discrimination has been admitted in cases involving jury selection and employment discrimination, focusing on factors such as gender, race, and age (see, e.g., Ashenfelter & Oaxaca, 1987;Castaneda v. Partida, 1977;Gunderson, 1989;Hazelwood School District v. United States, 1977;Gastwirth, 1984Gastwirth, , 1997Kaye, 1982;Lee, 1989: Shafritz, Hyde, & Rosenbloom, 1986.…”
Section: The Concept Of Disparate Impactmentioning
confidence: 99%
“…Ignoring the grand jurors carried over for a second year, however, would allow a county to intentionally discriminate against blacks in the carry over process, while appointing the minimal number of blacks in the new grand jurors needed to "pass" the standard binomial test. This is a general problem occurring when one is concerned with twostage employment practices, as shown in Gastwirth (1997) who studied methods for assessing the fairness of both hiring and promotion practices.…”
Section: Number Of Blacks On Grand Juries Of 18 In Colleton Countymentioning
confidence: 99%
“…Thus, different statistical methods will be preferred depending on the nature of the legal complaint. Gastwirth and Greenhouse (1995) and Gastwirth (1997) pointed out that the available sample size for studying the promotion process depends on the number of those who were hired. They showed that anomalous results can occur when one analyzes the data for the two processes separately.…”
Section: Introductionmentioning
confidence: 99%